Uma história movida a álcool: impactos ambientais no contexto canavieiro paulista (1975 a 2003) - Bertazi, Marcio Henrique [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The sugarcane, since its introduction in Brazil (after the rapid and voracious redwood trade) until the modern and specialized monoculture plantations, became an intrinsic and undeniable part of the Brazilian history, both in the economic sphere and in the imagination of successive generations. Generations those who watched an exponential income growth and an indelible depletion of natural resources, land concentration, rural migration and widespread unemployment. In this regard, the State of São Paulo gained relevance in the twentieth century, driven by the National Alcohol Program (Proálcool) and by the increase of alcohol demand in a context of global energy crisis. Consequently, the environmental impacts of the canicultor enterprise in this state. Although there is a great historical production on the issue of sugarcane in Brazil, including studies about Proálcool and its political, economic and social consequences, there is a significant lack of comprehensive surveys that map environmental impacts and put us in the lines of history. In this context, the analysis of the period extending from 1975 to 2003 revealed important movements in the Brazilian countryside, especially in the context of sugarcane in state of São Paulo. On one hand, there were established demands and trade-offs between country and city: the country pressed between the production of ethanol for domestic supply and the production of sugar for international market; and the city, which was as dependent of alcohol as Brazil was dependent of the oil in 1973. On the other hand, the social and environmental consequences become quite serious, among which: the intensification of the expulsion of rural workers to the cities with low locational infrastructure; atmospheric pollution and massive increase in the use of pesticides in the field, with direct consequences to the population health. In the analyzed period, however, there are...

De sua introdução no país, logo após o rápido e voraz comércio do pau-brasil, até as modernas e especializadas plantações monocultoras contemporâneas, a cana-de-açúcar tornou-se parte intrínseca e inegável da história do Brasil, não só na esfera econômica, mas no imaginário de sucessivas gerações que a acompanharam tanto como um fator de crescimento exponencial de renda como de depleção indelével dos recursos naturais, concentração de terras, migração rural e desemprego generalizado. O Programa Nacional do Álcool (Proálcool), decretado em 1975, fez com que os impactos socioambientais decorrentes do empreendimento canicultor intensificassem-se, em um contexto de crise energética de proporções mundiais. Nesse ínterim, o estado de São Paulo emergiu como um dos grandes produtores de açúcar e de álcool do país. Embora haja uma grande produção historiográfica a respeito da questão da cana-de-açúcar no país, inclusive quanto ao Proálcool e suas consequências políticas, econômicas e sociais, há uma ausência significativa de levantamentos abrangentes que mapeiem os impactos ambientais e coloquem-nos nas linhas da história. A análise do período que se estende de 1975 a 2003 revelou importantes movimentos no campo brasileiro, notadamente no contexto canavieiro do estado de São Paulo. Por um lado, observou-se o jogo de demandas que se estabeleceu entre o campo e a cidade: o campo pressionado entre a produção interna de álcool combustível e a exportação de açúcar no mercado internacional; e a cidade, cujo aumento da frota automobilística tornou-a tão dependente do álcool como estava do petróleo o Brasil em 1973. Por outro lado, as consequências socioambientais tornaram-se bastante graves, dentre as quais: intensificação da expulsão dos trabalhadores rurais em direção às cidades com baixo nível de infraestrutura locacional; poluição atmosférica...
Keywords: História ambiental; Cana-de-açúcar; Etanol; Encargos tributários sobre o impacto ambiental; Human ecology History